METHODS OF ORGANIZING MOVEMENT-BASED GAMES THAT DEVELOP THE COGNITIVE ABILITIES OF PRESCHOOL CHILDREN (European Journal of Interdisciplinary Research and Development, 2025)
This study explores the role of movement-based games in enhancing the cognitive development of preschool-aged children, focusing on the context of Uzbekistan. Early childhood is a critical period for cognitive growth, and physical activity plays a vital role in strengthening key cognitive functions such as working memory, attention control, and problem-solving.